Volume 4A: Dynamics, Vibration and Control 2013
DOI: 10.1115/imece2013-62989
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Feature Extraction Algorithms Based on Sonar Sensor Data

Abstract: Simultaneous localization and mapping (SLAM) is a technique used to determine the location of a mobile vehicle in an unknown environment, while constructing a map of the unknown environment at the same time. Mobile platforms, which make use of SLAM algorithms, have industrial applications in autonomous maintenance, such as the inspection of flaws and defects in oil pipelines and storage tanks. An important component of SLAM is feature extraction, which is the process of detecting and extracting significant fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This manuscript follows previous studies reported by the authors [13], [14]. The authors have organized the material into five sections.…”
Section: Indexmentioning
confidence: 87%
See 4 more Smart Citations
“…This manuscript follows previous studies reported by the authors [13], [14]. The authors have organized the material into five sections.…”
Section: Indexmentioning
confidence: 87%
“…By selecting a low threshold value for the TBF algorithm, it was ensured that no important features were removed. In an earlier study of the authors [13], it was shown that by increasing the threshold to a value above 100, a considerable number of the important features were removed, whereas for a threshold below a value of 100, no important features were lost. This observation is consistent with the conclusion drawn by Wijk and Christensen [18]; they used a low threshold value to avoid the removal of important features.…”
Section: A Environment I: L-shaped Environmentmentioning
confidence: 98%
See 3 more Smart Citations